Transcription factor IRF1 is responsible for IRF8-mediated IL-1β expression in reactive microglia - Takahiro Masuda; Shosuke Iwamoto; Satsuki Mikuriya; Hidetoshi Tozaki-Saitoh; Tomohiko Tamura; Makoto Tsuda; Kazuhide Inoue (Elsevier, 2015)
Interferon regulatory factor-8 (IRF8) plays a crucial role in the transformation of microglia to a reactive state by regulating the expression of various genes. In the present study, we show that IRF1 is required for IRF8-induced gene expression in microglia. Peripheral nerve injury induced IRF1 gene upregulation in the spinal microglia in an IRF8-dependent manner. IRF8 transduction in cultured microglia induced de novo gene expression of IRF1. Importantly, knockdown of the IRF1 gene in IRF8-transduced microglia prevented upregulation of interleukin-1β (IL-1β). Therefore, our findings suggest that expression of IL-1β is dependent on IRF1 in IRF8-expressing reactive microglia.